Cardinal Stanisław Hozjusz doctor in Utriusque Iuris – World Citizen - Szewczyk, Roman (Prawo Kanoniczne, 2024)
One of the most distinguished and greatest figures for the Roman Church and the Polish-Lithuanian Commonwealth in the 16th century is Cardinal Stanisław Hozjusz, Bishop of Warmia. The figure of Cardinal Hosius has gone down in great legends in the history of the Church and Poland. The multi-faceted activity of this outstanding Pole is assessed in many fields of his activity: royal official, poet, humanist, lawyer, theologian, MP, nuncio, theologian-polemist, defender of the Catholic faith, papal legate, cardinal. This is evidenced by the testimony of Pope Gregory XIII addressed to Fr. Stanisław Reszka after the funeral of the Bishop of Warmia: "We have lost the great column of the Church of God, the decoration of the college of cardinals and the splendor of our court. Now this holy cardinal will pray for us." Sixteenth-century Europe experienced great political, social and cultural changes that occurred during the life of Stanisław Hozjusz, which made him not afraid of dangers and challenges and made him appear on the map of Europe as a citizen of the world. A modern person may be surprised by the ease with which Stanisław Hozjusz, later as a bishop and cardinal, conquered the then areas of politics, culture and faith in Europe. Treating the world as a universe in which one could move freely was, however, a great challenge for that era. At the grave of Cardinal Hosius in Rome there is a beautiful sculpture, it is not known who made it, but we see a carved still life with books. On one of them there is an inscription: “Catholicus non est qui a Romania Ecclesia in fidei doctrina discordant” (He who does not agree with the Roman Church in matters of the doctrine of faith is not a citizen of the world. He who does not know the world is not a citizen, and above all after all, he is not a citize“ of the world, whom the world has not known.